Ultra-High-Resolution Monitoring of the Catchment Response to Changing Weather Conditions Using Online Sediment Trapping - Johansson M; Saarni S; Sorvari J (M D P I AG, 2022)
The purpose of this study was to identify relationships between meteorological and hydrological observations and sediment flux rate changes, in order to better understand catchment dynamics. The meteorological and hydrological observations included local air temperature, wind speed, water temperature, and ice cover, while the sediment flux rate was observed in the lake basin using a modified sediment trap technique. This study demonstrates the advantages of a new online methodology applied in conventional sediment trapping to obtain flux rate information with daily resolution. A prototype of a high-resolution online sediment trap was tested in Savilahti Bay, Lake Kallavesi, eastern Finland, during the period from 22 October 2017 to 6 October 2018. The daily resolutions of meteorological, hydrological, and sediment flux rate data were analyzed using statistical methods. The results indicate relationships between temperature, precipitation, wind speed, and sediment flux rate, but the urban site also showed erosional changes due to anthropogenic land use. Sediment flux ceased during winter season and spring floods were recorded as pronounced peaks in sediment flux, while the growing season showed generally higher sediment accumulation rates. This research also provides valuable information on the catchment response to short-term weather events. The influence of a storm led to larger sediment flux for several days. The importance of wind speed and frost formation on sedimentation, which has been difficult to address due to trap deployment times of typically several months, is now supported. Used together with varved sediment archives, online sediment trapping will facilitate the interpretation of paleoclimatic proxy records and modeling of detailed weather and erosion conditions that are related to climate change.